Technology Entrepreneurship Project (ENT 600) : Nike / Abdul Rahman Mat Kudin - Mat Kudin, Abdul Rahman (2021)
In this case study report, we have analysed the background company of Nike. Nike Company has been chosen causes it is one of the biggest and well-known sport brand in the world. So, I have undergone the research on this company based on theories and needs of their customers. The method that contains in this report is based on analysis of Customers Trends Canvas marketing strategy, innovation of footwear type and also SWOT analysis. The strength and weakness of this company can be identifying. By referring on this information, we develop based on society concerns on their problems. In this case, I have choose one Nike product which is Nike Elite socks as my subject to be innovate to become a better product that fulfil customer satisfaction and solve the problems that they faced when wear this product. By observing the result of data and finding that has been done, it shows that this Nike Elite socks have a few problems and negative feedback from their customers which when feel the discomfort and affected some part of their body especially ankle. Therefore, to overcome such problems, I has recommend few innovation for this socks to compete in the market. This new innovation will be able to satisfy the human need in protecting their foot from the risk of injury. Apart from that, the additional features will be able to reducing their daily life problems.